Enhancing the credibility of corporate climate pledges: Bringing climate transition plans and climate scenario analysis into the mainstream - Sayuri Shirai (Asian Development Bank Institute (ADBI), 2023)
In the face of the increasing frequency of climate change-related natural hazards and the resulting losses across the globe, companies are recognizing the importance of addressing climate-related risks and opportunities and taking timely actions to cope with them. While numerous large companies have committed to achieving net-zero greenhouse gas (GHG) emissions by 2050 or earlier, stakeholders are increasingly demanding greater transparency and credibility from these commitments. In response to a growing call for standardized, consistent disclosures that are essential for assessing corporate exposure to, and preparation for, climate change, the International Sustainability Standards Board (ISSB) released Climate-Related Disclosures in June 2023, based on well-established recommendations from the Task Force on Climate-related Financial Disclosures (TCFD). The ISSB's Standards are expected to be adopted by many countries as mandatory requirements for large companies. Specifically, disclosing GHG emissions data, including Scope 3 emissions in absolute amounts (excluding carbon credits), along with emissions reduction targets and a credible climate transition plan (roadmap), will become a crucial step for companies in demonstrating their unwavering commitment to their pledges. Additionally, conducting resilience assessments through climate scenario analysis is an essential component of corporate strategy. Corporate climate-related disclosures are evolving into an integral part of business strategies aimed at enhancing corporate value and gaining a competitive edge. This paper sheds light on identifying climate risks and opportunities and assessing their impacts, developing climate transition plans, and conducting climate scenario analyses.
Keywords: K22; M41; Q54; 330; corporate disclosure; climate transition plan; climate scenario analysis